Evolution of bone disease after kidney transplantation: A prospective histomorphometric analysis of trabecular and cortical bone. Issue 1 (January 2016) - Carvalho, Catarina; Magalhães, Juliana; Pereira, Luciano; Simões‐Silva, Liliana; Castro‐Ferreira, Inês; Frazão, João Miguel
Abstract: Aim: Post‐transplant bone disease results from multiple factors, including previous bone and mineral metabolism disturbances and effects from transplant‐related medications. Bone biopsy remains the gold‐standard diagnostic tool. Methods: We aimed to prospectively evaluate trabecular and cortical bone by histomorphometry after kidney transplantation. Seven patients, willing to perform follow‐up bone biopsy, were included in the study. Dual‐X‐ray absorptiometry and trans‐iliac bone biopsy were performed within the first 2 months after renal transplantation and repeated after 2–5 years of follow‐up. Results: Follow‐up biopsy revealed a significant decrease in osteoblast surface/bone surface (0.91 ± 0.81 to 0.47 ± 0.12%, P = 0.036), osteoblasts number/bone surface (0.45 (0.23, 0.94) to 0.00/mm 2, P = 0.018) and erosion surface/bone surface (3.75 ± 2.02 to 2.22 ± 1.38%, P = 0.044). A decrease in trabecular number (3.55 (1.81, 2.89) to 1.55/mm (1.24, 2.06), P = 0.018) and increase in trabecular separation (351.65 ± 135.04 to 541.79 ± 151.91 μm, P = 0.024) in follow‐up biopsy suggest loss in bone quantity. We found no significant differences in cortical analysis, except a reduction in external cortical osteonal eroded surface (5.76 (2.94, 13.97) to 3.29% (0.00, 6.67), P = 0.043). Correlations between bone histomorphometric and dual‐X‐ray absorptiometry parameters gave inconsistent results. Conclusions: The results show a reduction in bone activity, suggesting increased risk of adynamic bone and loss of bone volume. Cortical bone seems less affected by post‐transplant biological changes in the first years after kidney transplantation. Summary at a Glance: Definition of the changes in bone architecture post‐transplantation is difficult to obtain. In this study, the authors have managed to gather prospective biopsy data on a small group of transplanted patients, with clear definition of the changes.